Parental Knowledge and Attitude Regarding E-Cigarette Use in Saudi Arabia and the Effect of Parental Smoking: A Cross-Sectional Study - Sabbagh HJ; Khogeer LN; Hassan MHA; Allaf HK (Dove Medical Press, 2020)
Heba Jafar Sabbagh,1 Layla Nizar Khogeer,2 Mona Hassan Ahmed Hassan,3 Hanaa Khalil Allaf2 1Department of Pediatric Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 2Pediatric Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 3Department of Biostatistics, High Institute of Public Health, Alexandria University, Alexandria, EgyptCorrespondence: Heba Jafar SabbaghDepartment of Pediatric Dentistry, King Abdulaziz University, P.O. Box: 80200, Jeddah 21589, Saudi ArabiaTel +966 505668481Email hsabbagh@kau.edu.saIntroduction: E-cigarette use has been on the rise among children and adolescents. This study aimed to assess the knowledge and attitudes of the health hazards and laws regarding e-cigarette use among parents in Saudi Arabia. In addition, we evaluated the effect of parental smoking on parent’s knowledge.Methods: This study was conducted with parents of children below 18 years of age in Jeddah, Saudi Arabia. Jeddah was divided into four areas (north, south, east, and west) and in each area, the largest shopping mall was selected. Data were gathered using a self-administered questionnaire.Results: Out of 1386 parents, 61.7% were smokers, 13.3% reported that their children used e-cigarettes, and 73.6% did not discuss e-cigarette use with their children. In total, 77.3% of parents thought it was important to be educated about e-cigarette use. However, their ability to discuss e-cigarette use with their children was 13.9% lower than their ability to discuss regular cigarette smoking with their children. Parents who were smokers were more accepting of their children using e-cigarettes (P< 0.0001). Mothers who smoked were more accepting than fathers of their children using e-cigarettes (P< 0.0001).Conclusion: Parents reported a lack of knowledge and attitudes regarding e-cigarette use. Parental smoking, especially among mothers, was statistically significantly related to their e-cigarette use knowledge and attitudes. Parents agreed that it was important to educate parents regarding e-cigarette use.Keywords: electronic-cigarette, smoking, Saudi Arabia, parental smoking